Mutational Profile of Metastatic Pheochromocytoma and Paraganglioma - Choi, Yun Mi (J Endocr Soc, 2021)
Background: In pheochromocytoma and paraganglioma (PPGL), germline and somatic mutations in one of the known susceptibility genes are present in about 60% of tumors. However, the genetic events that drive the malignant progression of the disease are yet poorly understood. We aimed to evaluate the mutational profiles of metastatic PPGLs by targeted next-generation sequencing (NGS) to characterize the genetic events in metastatic PPGLs. Methods: Among the previously reported metastatic PPGL series from Asan Medical Center (AMC), Seoul, Korea, fifteen patients with available formalin-fixed, paraffin embedded (FFPE) archival samples for targeted exome sequencing were enrolled in this study. We also analyzed accessible data of aggressive PPGLs from The Cancer Genome Atlas (TCGA) and compared with findings of AMC samples. Results: A total of 115 germline and 34 somatic variants were identified in AMC cohort. Tumors of AMC cohort had median 0.58 per megabase tumor mutation burden. Most frequently mutated mutations were SDHB germline mutation (27%), and SETD2, NF1, HRAS somatic mutations (13%). Genes are subtyped into pseudohypoxia group (n=5), kinase group (n=5) and unknown (n=5) group. In unknown subgroup, two samples showed ATRX mutations and one accompanied SETD2 mutation. In copy number variation analysis, the most frequently observed pattern was deletion of 1p arm where SDHB is present. In survival analysis, SDHB mutation and pseudohypoxia subtype was significantly associated with poor prognosis. Conclusion: The analysis of NGS from patients with metastatic PPGLs demonstrated rare genetic events as well as well-known mutations. The pseudohypoxia subtype presented poor prognosis than kinase or unknown subtypes. Subjects who had no deletion in 1p arm showed favorable treatment response. Further studies to discover driver events and markers of metastasis are warranted.